Co-production and innovation in public services’ assessment: The case of the Citizen Audit Project - Squio, Clóvis Renato; Hoffmann, Micheline Gaia (Revista de Administração da UFSM, 2021)
Purpose: This paper analyzes the Citizen Audit Project (PAC), in the light of public sector innovation theory, in order to identify challenges for introducing co-production in the evaluation process of public services by the internal audit of the Executive Power of the State of Santa Catarina, Brazil. Design/methodology/approach: We carried out the study as a qualitative research, and collected data through a documentary search and interviews with 21 key agents of public control or with those who interacted with PAC in the chosen operations. We used content analysis to examine the collected data. Findings: We analyze the main challenges inherent to co-production in the activity of public services’ assessment by internal audit. Results show an alignment between the identified dares and the theoretical basis of public innovation. These were barriers related to bureaucratic dysfunctions, openness of political agents and audit professionals to receive and consider proposals from society, time and resources needed, leadership style, citizens’ lack of motivation, and the evaluation model. Originality/value/implications: The paper contributes to the literature on public audit, public sector innovation, and co-production, by conducting an original study that identified challenges related to the implementation of co-production in audit process and analyzed them from the perspective of public sector innovation. Evidence brought by this research contributes to fill literature gaps regarding empirical studies on the convergence between these three topics. Regarding practical implications, it provides base for PAC consolidation and for its replication by governments interested in implementing innovations through the process of participatory audit.